2016
DOI: 10.12740/pp/58771
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of self-reported insomnia in general population of Poland

Abstract: Study results suggest that self-reported insomnia is a common problem in general population of Poland. The most common sleep problem is impaired sleep initiation. Insomnia complaints are most prevalent in women and in the older age groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 14 publications
2
38
1
3
Order By: Relevance
“…Insomnia is one of the sleep disorders defined as unsatisfactory quality and quantity of sleep that is associated with difficulty in falling asleep, maintaining sleep and early waking . According to Nowicki et al , more than half of the Polish population declares subjective insomnia. In our own study, as many as 83% of respondents suffered from insomnia.…”
Section: Discussionmentioning
confidence: 99%
“…Insomnia is one of the sleep disorders defined as unsatisfactory quality and quantity of sleep that is associated with difficulty in falling asleep, maintaining sleep and early waking . According to Nowicki et al , more than half of the Polish population declares subjective insomnia. In our own study, as many as 83% of respondents suffered from insomnia.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the prevalence of sleep disturbances as measured by the presence (yes/no) of any sleep complaint (DIS, DMS, EMA or NRS) ranges between 1.6 and 76.3% in the general population (Kim et al ., ; Ohayon and Paiva, ; Ohayon and Sagales, ; Ohayon and Smirne, ; Ohayon et al ., ; Rocha et al ., ). In contrast, the prevalence of sleep disturbances as defined by dissatisfaction with sleep quality or quantity, or subjective poor sleep ranges between 7.0 and 50.5% (Nowicki et al ., ; Ohayon, ; Ohayon and Paiva, ; Ohayon and Partinen, ; Ohayon and Smirne, ; Ohayon et al ., ). Using screening instruments such as the Pittsburgh Sleep Quality Index (PSQI) or the Athens Insomnia Scale (AIS), the prevalence of sleep disturbances ranges between 25.3 and 38.2% (Madrid et al ., ; Paparrigopoulos et al ., ; Soldatos et al ., ).…”
Section: Introductionmentioning
confidence: 98%
“…General population studies in numerous countries have reported that insomnia affects 15.8–57% of adults (Adams et al, ; Beck, Richard, & Leger, ; Morin & Benca, ; Nowicki et al, ). The prevalence of insomnia is affected by the definition and measurement tools being used.…”
Section: Introductionmentioning
confidence: 99%